Detection of fire by comparison of sampling coefficients of variation of current measurements of dangerous parameters of the gas environment - Tolok, Igor; Pospelov, Boris; Rybka, Evgenіy; Iatsyshyn, Andrii; Kozar, Yurii; Krainiukov, Olekcii; Morozov, Ihor; Bezuhla, Yuliia; Kravtsov, Mikhail; Salamatina, Olga (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the selective coefficient of variation of dangerous parameters of the gas environment, which are caused by the general aggregates of reliable absence or occurrence of ignition of materials. The method of prompt detection of fires based on the comparison of the sample coefficients of variation of the hazardous parameters of the gas environment of the specified general populations and the verification for each moment of time of the result of the comparison of the sample coefficients of variation and exceeding the current threshold is theoretically substantiated. At the same time, the value of the current threshold is calculated taking into account the given probability of false detection of ignition and the current error of the result of comparing the sample coefficients of variation. This method makes it possible to ensure the maximum current probability of correct ignition detection. Experiments were conducted to verify the performance of the proposed method. The obtained results in general indicate the efficiency of the method. It was established that the result of the comparison of the sample coefficients of variation of the hazardous parameters of the gas environment, which correspond to the specified general populations for carbon monoxide at the time of ignition of alcohol, paper, wood, and textiles, is 0.47, 0.14, 0.2, and 0.001, respectively. For the temperature, the results of the comparison of the sample coefficients of variation during the ignition of similar materials are 0.12, 0.13, 0.015 and 0.045, respectively. At the same time, for prompt detection of fires based on the proposed method, it is necessary to preferably use the concentration of carbon monoxide and the temperature of the gas environment as dangerous parameters of the gas environment. The practical importance of the research is the use of selective coefficients of hazardous parameters of the gas environment for the detection of material fires in real time